Enzalutamide + androgen deprivation therapy (ADT) versus flutamide + ADT in Japanese men with castration‐resistant prostate cancer: AFTERCAB study. Issue 1 (20th August 2021) - Uemura, Hiroji; Kobayashi, Kazuki; Yokomizo, Akira; Hinotsu, Shiro; Horie, Shigeo; Kakehi, Yoshiyuki; Naito, Seiji; Nonomura, Norio; Ogawa, Osamu; Oya, Mototsugu; Suzuki, Kazuhiro; Saito, Atsushi; et al.
Abstract: Objectives: The objective of the study is to compare the efficacy and safety of alternative androgen therapy (AAT) with enzalutamide + androgen deprivation therapy (ADT) and flutamide + ADT in the treatment of Japanese men with metastatic or nonmetastatic castration‐resistant prostate cancer (CRPC) who progressed despite combined androgen blockade (CAB) with bicalutamide + ADT. AAT treatment sequence was also investigated. Materials and methods: The open‐label, Phase 4 AFTERCAB study (NCT02918968) was conducted from November 2016 to March 2020 in Japanese men aged ≥20 years with asymptomatic or mildly symptomatic CRPC. Patients were initially randomized to enzalutamide (160 mg/day) + ADT (enzalutamide first) or flutamide (375mg/day [125mg three times daily]) + ADT (flutamide first) as first‐line therapy. Following prostate‐specific antigen (PSA) progression, other disease progression, or discontinuation of first‐line therapy due to an adverse event (AE), patients switched to the other treatment as second‐line therapy. The primary endpoint was time to PSA progression with first‐line therapy (TTPP1). Secondary endpoints included TTPP2 (TTPP1 + time to PSA progression with second‐line therapy). AEs were monitored to assess safety. Results: Overall, 206 men were randomized (enzalutamide first, n  = 102; flutamide first, n  = 104) and stratified by study site and disease stage; 133 patients transitioned to second‐line therapy (enzalutamide first, n  = 48; flutamide first, n  = 85). TTPP1 was significantly improved with enzalutamide first versus flutamide first (median 21.4 months vs. 5.8 months; hazard ratio [HR] 0.42; 95% confidence interval [CI] [0.29, 0.61]). TTPP2 was numerically improved with enzalutamide first versus flutamide first (median not reached vs. 21.2 months; HR 0.76; 95% CI [0.48, 1.19]). Both treatments were generally well tolerated, with AEs consistent with their known safety profiles. Conclusion: First‐line AAT with enzalutamide + ADT provided a significant improvement in time to PSA progression versus flutamide + ADT. Enzalutamide + ADT may therefore be the preferred first‐line AAT option in Japanese men with metastatic or nonmetastatic CRPC who progress despite CAB with bicalutamide + ADT.